2002
DOI: 10.1542/peds.109.5.e83
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrician Counseling About Preventive Health Topics: Results From the Physicians’ Practices Survey, 1998–1999

Abstract: ABSTRACT. Objective. Government agencies and national organizations recommend that physicians counsel their child and adolescent patients about preventive health topics. Using data from a national survey, we describe the counseling patterns of pediatricians in regard to 9 recommended preventive health topics.Methodology. Between October 1998 and April 1999, information was collected from 907 of 1760 primary care pediatricians randomly selected from a nationally representative sample. Through either a telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 30 publications
8
69
0
Order By: Relevance
“…35 Despite these recommendations, there are gaps in the delivery of anticipatory guidance to reduce tobacco smoke exposure. [36][37][38] Moreover, even when screening and counseling occurs, most smoking parents are not provided resources for tobacco cessation. 39 On the basis of a survey of providers of pediatric care, Kaplan et al 40 concluded that improvements are needed to optimize delivery of smoking cessation guidance to adolescents.…”
Section: Figurementioning
confidence: 99%
“…35 Despite these recommendations, there are gaps in the delivery of anticipatory guidance to reduce tobacco smoke exposure. [36][37][38] Moreover, even when screening and counseling occurs, most smoking parents are not provided resources for tobacco cessation. 39 On the basis of a survey of providers of pediatric care, Kaplan et al 40 concluded that improvements are needed to optimize delivery of smoking cessation guidance to adolescents.…”
Section: Figurementioning
confidence: 99%
“…3,[5][6][7][8][9][10][11] The initial questionnaire was pilot tested on 6 practicing family physicians, revised, and then retested on 20 practicing family physicians. Postage-paid reply envelopes were consecutively numbered to allow clerical staff to track response rates.…”
Section: Methodsmentioning
confidence: 99%
“…2 Providing anticipatory guidance on a broad range of topics can be time consuming and logistically difficult. 3 Issues of prevention and guidance are often given limited attention because of the broad agenda of the well-child visit. 4,5 Previous studies have evaluated pediatricians' anticipatory guidance preferences 6 as well as parental expectations.…”
mentioning
confidence: 99%
“…18 Physician-initiated safety discussions to prevent vehicle injury, improve diet, and reduce drug use have become commonplace. 19 So what, if anything, characterizes the prevention of gun injuries as beyond the physician's concern?…”
Section: Textmentioning
confidence: 99%